The prognostic relevance of oxygen uptake in inoperable chronic thromboembolic pulmonary hypertension. (3rd November 2015) - Richter, Manuel Jonas; Pader, Philip; Gall, Henning; Reichenberger, Frank; Seeger, Werner; Mayer, Eckhard; Guth, Stefan; Kramm, Thorsten; Grimminger, Friedrich; Ghofrani, Hossein A.; Voswinckel, Robert
Abstract: Background: Patients with chronic thromboembolic pulmonary hypertension (CTEPH) present with a decreased oxygen uptake, however, the prognostic relevance of oxygen uptake (VO2 ) in inoperable CTEPH is unknown. Methods: Patients with inoperable CTEPH were retrospectively analyzed. All patients were assessed by means of right heart catheterisation and cardio pulmonary exercise testing in semisupine position with a 30 Watt increment step‐protocol. Results: One‐hundred and fifty‐one patients (82 female (54.3%), mean age 61 ± 12.4 years) presented with a mean pulmonary arterial pressure of 40.2 ± 14.2 mmHg and pulmonary vascular resistance (PVR) of 641.9 ± 374.8 dyne∗s/cm 5 . The peak VO2 (mean 13.1 ± 4.5 mL∗kg −1 ∗min −1 ) was measured at initial referral. Over a follow‐up of up to 10 years (mean 4.41 ± 2.57 years), 31 patients had died. Patients with a baseline peak VO2  ≥ 10.7 mL∗kg −1 ∗min −1 [area under the receiver‐operating characteristic curve (AUC) = 0.728, P  = 0.001] had better survival than those with a peak VO2  ≤ 10.7 mL∗kg −1 ∗min −1 using Kaplan–Meier analysis (88.8% vs 60.1%; log rank P  = 0.001). Adjusting for age, gender and PVR, multivariate analysis identified peak VO2 as a predictor of mortality [hazard ratio (HR): 2.78, 95% CI 1.01–7.63, P  = 0.047]. In addition, peak VO2 failed as an independent prognostic factor in a stepwise multivariate model including all variables significant in the univariate analysis. Conclusions: In patients with inoperable CTEPH the peak VO2 is a significant predictor of survival, when adjusting for age, gender and PVR. However, peak VO2 failed as an independent prognostic factor when correcting for all significant baseline variables, which is limiting the clinical usability.